2011
DOI: 10.1007/s00213-011-2570-3
|View full text |Cite
|
Sign up to set email alerts
|

Schedule-induced polydipsia as a model of compulsive behavior: neuropharmacological and neuroendocrine bases

Abstract: SIP represents an animal model of non-regulatory and excessive drinking that may be valid for studying the psychopharmacology of the compulsive phenotype and modeling different psychopathologies from compulsivity spectrum disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 116 publications
5
90
0
1
Order By: Relevance
“…Taken together, these results suggest that CFL induced by dopaminergic drugs models some key hallmarks of the obsessive-compulsive disorder (OCD) in that the contingent response is excessive, time consuming, and disconnected to the outcome it is performed for. Our findings are in line with the notion that dopaminergic stimulation enhances compulsive drinking during schedule-induced polydipsia (SIP), a reliable model of OCD whereby rats drink in excess of need following intermittent food presentation (Platt et al 2008;Moreno and Flores 2012;Hawken and Beninger 2014).…”
Section: Introductionsupporting
confidence: 89%
“…Taken together, these results suggest that CFL induced by dopaminergic drugs models some key hallmarks of the obsessive-compulsive disorder (OCD) in that the contingent response is excessive, time consuming, and disconnected to the outcome it is performed for. Our findings are in line with the notion that dopaminergic stimulation enhances compulsive drinking during schedule-induced polydipsia (SIP), a reliable model of OCD whereby rats drink in excess of need following intermittent food presentation (Platt et al 2008;Moreno and Flores 2012;Hawken and Beninger 2014).…”
Section: Introductionsupporting
confidence: 89%
“…SIP therefore has several features of the compulsions observed in OCD and related illnesses. As suggested by Moreno and Flores (2012), consideration of the variables affecting SIP and the neurocircuitry underlying this maladaptive behavior may provide novel insights into OCD.…”
Section: Insights Into Ocd From Animal Models Of Enhanced Schedulementioning
confidence: 99%
“…It is not necessary to require an operant response of the animal in order to observe SIP; Falk (1969) showed that presenting response-independent food pellets at the same inter-pellet intervals that were used in the VI 1-min schedule described above led to the same level of SIP as that observed when a response was required. Fixed-time (FT) schedules of response-independent food presentations produce optimal SIP when the inter-pellet interval is 60 s (see Moreno and Flores, 2012). …”
Section: Insights Into Ocd From Animal Models Of Enhanced Schedulementioning
confidence: 99%
See 2 more Smart Citations